Jordanian nursing students’ perceptions of the compassionate actions of their clinical instructors: a mixed-methods study - Rabia H. Haddad; Fatimah S. Tarawneh; Raya Y. Al-Husban; Salam Bani Hani; Bushra Kh. Alhusamiah; Shefa’a Alfraheed; Renait Haddad; Alaa Abu Attallah; Haya Qattom; Ashraf Jehad Abuejheisheh (BMC Nursing)
Abstract Background In helping professions such as nursing, caring is regarded as a fundamental principle. Observations of nursing students revealed both caring and non-caring behaviors, highlighting the complexity of professional development within clinical and educational settings. Aim This study sought to understand how Jordanian nursing students perceived the caring behavior of clinical instructors during their clinical training. Method A mixed-methods approach was utilized to recruit data from (n = 200) nursing students using the Nursing Students’ Perception of Instructor Caring (NCPIC) developed by Wade and Kasper (2006). Result The findings showed that the average mean score for clinical instructor behaviors perceived by nursing students was at a medium level (M = 3.40 out of 6). Four themes were extracted, namely, communication, professionalism, holistic caring (mothering), and motivation. In contrast, the non-caring behaviors were reflected in poor communication, governing, and unfavorable personal traits of the clinical instructors, as well as acting in a non-professional manner. Conclusion Caring has been emphasized as a key component of nursing education. It should be inherent in the behavior and actions of clinical instructors when they interact with nursing students in a clinical setting. Clinical trial number Not applicable.